Pandemi dalam Worldview Islam; Dari Konsepsi ke Konspirasi - Maulana, Abdullah Muslich Rizal (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2020)
In order to face the challenge of COVID-19 Pandemic, Muslims are demanded to execute Health Protocols in accordance with the Worldview of Islam. Through the conceptualization of ‘Pandemic’ in Worldview of Islam, Muslims are able to find several crucial elements constructing ‘Pandemic’ based on a proper comprehension of their Theological Foundation. This paper will re-examine the concept of Pandemic utilizing Worldview of Islam as an analytical framework; started from an enquiry of Pandemic concept in Quran and Prophetic Tradition, altogether with a reflection from the great legacy of Islamic Civilization in Medical Issues. As such, some issues related to the ‘conspiracy theory’ related to COVID-19 will also discussed, before finally ended with a brief note regarding ‘New Normal’ code.